Clinical Cases in Neurology - Dolezal, Ondrej; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This new second edition presents a completely new selection of 25 scenarios based on cases from the personal archive of Ondrej Dolezal, collected over 20 years of clinical practice. With a simple and uniquely innovative approach, this book offers a natural workflow through the chapter structure, helping junior doctors to gain confidence in reaching their clinical diagnosis. A range of different clinical scenarios and neurological conditions are examined, from cerebal palsy and other degenerative disorders, to epilepsy and headache. This book can serve as a teaching aid in a classroom setting, where the teacher introduces the case (2telling the story3, neurological examination) and the students then propose differential diagnoses and further tests. The teacher can show a representative test result to students and expect them to interpret the scan/test, as well as proposing further referrals and discussing the prognosis. Each chapter, contains visual aids in the form of Neuroexam, helping the reader gain a quick understanding of the case. Scenarios presented in this book can be used at the bedside in teaching medical students and junior doctors, and it is aimed at trainee neurologists and any non-neurologists who might encounter neurological cases in the clinic. .
Introduction -- Paresthesia in hand and clumsiness -- Anaemia and ankle weakness -- Twitching in the face and tingling -- Unconscious young woman -- Post-Seizure Confusion and Head Injury -- Extrapyramidal, cerebellar and Cognitive symptoms in an older man -- Unsteadiness and Stiff Neck in a Young Man -- Tingling in the Face -- Generally unwell man -- Numbness of face and tongue -- Not seeing the whole picture -- Falls in cerebral palsy -- Leg pain in young man with diabetes -- Waxing and Waning hand weakness -- Not feeling the heat -- Burning legs -- Progressive weakness -- Confusion, Hemiparesis in a Young Woman with squint -- Two seizures and strong family history of epilepsy -- Cough and strain headaches with nausea -- New Headache in an elderly patient -- Only sensory symptoms -- Only sensory symptoms II -- Only sensory symptoms III -- New double vision and cancer history.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Neurology .; Radiology; Family medicine; Neurology; Radiology; General Practice and Family Medicine